Corpora in ESP/EAP writing instruction preparation, exploitation, analysis - Charles, Maggie; Frankenberg-Garcia, Ana (New York, NY : Routledge, 2021)
This collection showcases the latest innovations in research on the application of corpora and corpus-based methods in ESP/EAP writing instruction and the many ways in which corpora can be successfully and practically integrated in ESP/EAP programmes. While previous work has discussed the successful use of corpora in teaching writing in the areas of ESP/EAP, this book is the first of its kind to bring the most up-to-date research on the topic together in one place. The volume's unique structure mirrors the key stages of the writing instruction process, from preparation to exploitation to analysis. The book begins by showing how corpora can be used to prepare materials, moving into an exploration of how students in ESP/EAP programmes use corpora in practice, before bringing the discussion full circle to the ways in which corpus-based approaches might be implemented to analyse ESP/EAP student writing. This approach presents readers with insights into how corpora can be effectively integrated into ESP/EAP writing instruction at every step of the process and opens the way for future areas of study. This book will be of particular interest to students and researchers in applied corpus linguistics, English for Specific Purposes, and English for Academic Purposes, as well as active practitioners in ESP/EAP writing instruction.
Dichotomies and debates in corpora and ESP/EAP writing / Maggie Charles & Ana Frankenberg-Garcia -- Exploiting corpora to provide guidance for academic writing : the BAWE Quicklinks project / Benet Vincent, Hilary Nesi & Daniel Quinn -- Discipline-specific academic phraseology : corpus evidence and potential applications / Geraint Paul Rees -- Exploring the relationships between English writing motivation and uptake of corpus-aided corrective feedback : a longitudinal study / Hsien-Chin Liou & Szu-Yu Liu -- Exploiting a genre-specific corpus in ESP writing : students' preferences and strategies / Katherine Ackerley -- Undergraduate students' responses to a corpus-based ESP course with DIY corpora / Reka R. Jablonkai & Neva Čebron -- The use of stance in L2 first-year college writing : its relation to genre, revision, and writer characteristics / Ji-young Shin -- Identifying collocation issues in English L2 research article writing / Paula Tavares Pinto, Geraint Paul Rees & Ana Frankenberg-Garcia.
OCLC-licensed vendor bibliographic record.
Keywords: English language -- Study and teaching (Higher) -- Foreign speakers; Academic writing -- Study and teaching; Report writing -- Study and teaching (Higher); Corpora (Linguistics); Second language acquisition; LANGUAGE ARTS & DISCIPLINES / Linguistics